Prevalence and correlates of anxiety disorders and depressive disorders among older adults with non-communicable diseases: results from China Mental Health Survey - Ge, Hongmin; Liu, Zhaorui; Tong, Yue; Huang, Yueqin; Hou, Xiaofei; Li, Minghui; Yan, Yongping; Xiao, Shuiyuan; Li, Lingjiang; Zhang, Tingting; Yan, Jie; Yu, Yaqin; et al. (Frontiers in Psychiatry, 2025)
BackgroundAnxiety disorders (ADs) and depressive disorders (DDs) are prevalent among older adults with non-communicable diseases (NCDs), yet nationally representative epidemiological data from China remain limited. This study, as a part of the 2013–2015 China Mental Health Survey (CMHS), aimed to assess the prevalence of ADs and DDs and identify associated factors among older adults with NCDs in China.MethodA total of 5,428 patients aged 60 years and above with reported NCDs were selected from the CMHS. The Composite International Diagnostic Interview (CIDI) was used to diagnose ADs, DDs, and alcohol use disorders (AUDs) in order to assess their disease status and the lifetime and 12-month prevalence. Data were weighted by age, sex, and residential distribution from the 2010 Chinese census to correct for selection probabilities and response rates, and were post-stratified for national representativeness. Univariate and multivariate logistic regression was used to identify factors associated with 12-month ADs and DDs.ResultThe lifetime prevalence of ADs was 8.3% and the 12-month prevalence of ADs was 5.8%. The two most prevalent ADs were specific phobia (SP; lifetime prevalence of 4.2% and 12-month prevalence of 3.1%) and obsessive-compulsive disorder (OCD; lifetime prevalence of 2.8% and 12-month prevalence of 2.1%). The lifetime prevalence of DDs was 10.1%, while the 12-month prevalence was 5.4%. The two most common DDs were major depressive disorder (MDD; lifetime prevalence of 7.2% and 12-month prevalence of 4.4%) and dysthymia (lifetime prevalence of 2.8% and 12-month prevalence of 2.2%). ADs are most common in individuals with heart attacks (12%), chronic lung disease (11.2%), and other chronic pain (11%). DDs are most commonly linked to heart attacks (13.8%), other chronic pain (13.2%), and cancer (13.1%). Female gender, alcohol use disorder, and comorbid with three or more NCDs were found to be risk factors associated with ADs and DDs.ConclusionThe co- occurrence of mental disorders among older adults with NCDs has become a growing public health concern in China. Primary health care institutions and clinicians should simultaneously enhance the management of chronic NCDs and mental health care among older adults.